THE EFFECT OF SELF-ASSESSMENT STRATEGY AND SELF-EFFICACY ON STUDENTS’ WRITING COMPETENCY - Yudha Paramartha, A. A. Gede (Jurnal Pendidikan dan Pembelajaran Bahasa Indonesia, 2012)
In language teaching and learning, the language uses are categorized into four skills which have to be mastered by students. They are reading, writing, listening, and speaking skills. Besides, students also have to master language aspects, such as vocabulary, pronunciation, and grammar. All of those language aspects should be taught integratedly with the four language skills. Then, it is expected that students are able to use the target language appropriately in their daily life.Writing as one aspect of those skills is important to be learnt by students. Orwig (1998) defines writing as an indirect communication between reader and writer which involves communicating thoughts of the writer that is conveyed on the text. Indirect communication means that the communication is not carried out face to face. Thus, it is done through texts. Writing is important because of some reasons. First, writing ability is a basic foundation for learners to support their success in academic life. Nowadays, many school assignments are in the form of written assignments. It is because students? competency can be seen from their writing performance. Second, for their future, writing can contribute to their career. Many job vacancies require ability of writing well, especially in English. For example, a news maker needs writing to report what he has seen on the field. Another example, a secretary has to be able to make a written report and write messages both in Bahasa Indonesia and in English.Writing is often considered as the most difficult language skill to be learnt since its complexity makes it becomes difficult. Not only in the matter of linguistic ability, writing also involves various cognitive and creativity process. In cognitive process of writing, writing is viewed as a process of transaction between writer schemes which consist of variety of information. In creative process of writing, the writing process is characterized by the insight of unique new ideas which is logically and uniquely arranged in writing (Marhaeni, 2010).Other aspects to become challenging for students are also found related to the structural rules of writing. It involves the dimension of content and development, vocabulary and style, grammar and structure, and the generic structures. Related to content and development, students find it difficult to develop their ideas and to organize them to make it coherent. Students often get confused to develop their paragraphs like which supporting details are appropriate to be put to support the controlling idea. The decision whether they have put sufficient ideas on the text is also another problem faced by them. The mechanic of writing also becomes frequent problems. For example, students often make mistakes in punctuation such as putting commas, full stops, semi colons, etc. Moreover, they also get confused to develop ideas based on the generic structures.A text is not only read by the writer writing the text. Thus, he also has to take into account about their readers. He has to consider what subject that the readers likely want to know, how much he needs to explain something, how to make it persuasive and enjoyable, what has to be explicit, and what can be left implicit. Those questions are some of many considerations which make writing difficult.To facilitate the students to be a good writer is not an easy job. Generally, students tend to be not sure about what they write or what they revise. It is because there are some considerations in writing that students may not be sure that they can fulfill all of them. Some of the considerations are in terms of grammar, idea development, generic structures, appropriate tenses, coherency, unity of the writing, and so forth. Teacher should accommodate students with a kind of tool to overcome students? difficulty. The key point to do is that the teacher should treat the students that they will be sure about what they have made. To make it happen, teaching strategies to accommodate their writing are considered essential. By having appropriate evaluations, the students can understand which part of their writing that is considered incorrect or need revision. Then, they can make some revisions and learn from their mistakes.One type of the evaluation is having feedbacks of what they have written. Students need feedback to evaluate their own writing. By having some feedback, it is expected that the students can construct their belief in his or her ability to be successful in writing. Besides having feedbacks, students need help to develop their own writing. It can be done by activating their metacognitive awareness of what they are writing (Oscarson, 1989 in Oscarson, 1997)). One way to develop their awareness of metacognition is by giving them a treatment which enables them to monitor themselves when they are writing. It can help students develop knowledge through conscious control over the knowledge or to develop metacognitive awareness of knowledge and thought. Considering this factor, self-assessment is applicable for them when writing.Self-assessment can promote learning in writing because it gives learners training in evaluation which is important for autonomous learning. Learners need to be able to make reliable and valid judgments. When learner are asked questions about what and how they have learnt, it fosters evaluative attitudes in the learners and improve goal-orientation because the learners are aware of variability of language learning objectives and they are in control of their own learning situation (Black et al., 2004).Self-assessment can be conducted not only for assessment strategy; it also can be used for teaching strategy. Self-assessment as teaching strategy can focus students and emphasize assessment as a process of metacognition (Earl & Katz, 2006). It comes from the idea that learning is not just a matter of transferring ideas from someone who is knowledgeable to someone who is not, but it is an active cognitive process that occurs when they interact with new ideas. Thus, self-assessment as a teaching and learning strategy can bring benefits in which students will become aware of monitoring what they learn, and can make adjustment, adaptation, improvement, and change in their thinking (Earl & Katz, 2006).Feedbacks in writing that the students get by doing self-assessment will be meaningful if students have beliefs that they are able to assess the writing. If they do not have any kind of belief, the quality of their assessment can be considered questionable (Aliegro, 2006). In line with this, a research done by Lavelle & Zuercher (1999) stated that students? belief in their ability in writing could affect the students writing competency. Students with low belief in their writing reported that writing was a very painful experience and it also affected their competency in writing.Considering that the students? belief in their ability in writing can influence their success in writing, it is important to consider students? self-efficacy which affects students? capability to do evaluation on their writing and students? writing competency. Self-efficacy is a person?s belief in his or her ability to succeed in a particular situation (Bandura, 1995). It is a person?s belief in their own competence. One who has a high level of self-efficacy is capable of performing in a certain manner to achieve certain goal. Related to writing, self-efficacy is the students? belief about their ability to be successful in doing the task of writing.Students tend to take a writing task if they believe they can succeed. They generally avoid tasks if their self-efficacy is low, but will engage in tasks where their self-efficacy is high. Related to their actual ability, students with a self-efficacy significantly beyond their actual ability often overestimate their ability to complete tasks, which can lead to difficulties. On the other hand, students with a self-efficacy significantly lower than their ability are unlikely to grow and expand their skills (Lavelle & Zuercher, 1999).In conclusion, the positive relation among self-efficacy, self-assessment strategy, and writing is that students will be able to assess their own writing confidently and effectively if they have a belief that they are capable to do so. Therefore, treating students with self assessment strategy with the consideration of self-efficacy is predicted to bring a positive value to the development of students? writing competency. Thus, it is very urgent to see the effect of self-assessment strategy, and students? self-efficacy on students? English writing competency.Identification of the ProblemThe success in learning can be determined by internal and external factors of the students. The internal factors include intelligence, giftedness, cognitive styles, thinking styles, adoption resources, adversity, initial ability, motivation, anxiety, and self-efficacy. On the other hand, the external factors include teacher factors, the factor of learning processes and environmental factors.In accordance to the present research, the factors which are considered important to be investigated to improve students? writing competency are students? self-efficacy as internal factor and self-assessment strategy as external factor. Thus, the problem arising is to investigate the effect of self-assessment strategy on students writing competency, the interactional effect between self-assessment strategy and self-efficacy, the difference in writing competency between high self-efficacy students who are treated by using self-assessment strategy and those who are treated by using conventional strategy, and the difference in writing competency between low self-efficacy students who are treated by using self-assessment strategy and those who are treated by using conventional strategy.The conventional strategy for this research is predicted as an insignificant strategy for developing students? writing competency. On the other hand, the use of self-assessment strategy is predicted to give a positive effect on students? writing competency.